Specification for portland-blastfurnace cement Part 2 . Metric units (BSI, 1973)
Portland cement, Cements, Blast-furnace cement, Cement and concrete technology, Aggregates, Composition, Chemical composition, Production, Testing, Compressive strength, SI system (metric), Quality, Setting